PENGARUH BEBAN KERJA, JOB INSECURITY DAN GAYA KEPEMIMPINAN TERHADAP TURNOVER INTENTION (Studi Pada Petugas Penyuluh Lapangan Pt Panca Patriot Prima Cabang Yogyakarta) - Hidayat, Muhamad Rizki; Rohyani, Indah (Bajang Institute, 2025)
This research conducted in order to find out the effect of Workload, Job Insecurity, and Leadhership Style on Turnover Intention (Study on field extension officer of PT Panca Patriot Prima in Yogyakarta). The population used were all extension officer in PT Panca Patriot Prima in Yogyakarta and the sampling technique were carried outthrough non- probability sampling method, it was namely assaturated sampleswith a total of 40 extension officer. This research was using analysis tools SPSS 21 software. Data analysis used isvalidity and reliability test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results of this study showed that Workloadhas a significant effect on Turnover Intention, Job Insecurity a significant effect on Turnover Intention, and Leadhership Style has a significant effect on Turnover Intention. Whereas,Workload, Job Insecurity, and Leadhership Style have a significant effect on Turnover Intention